2011
DOI: 10.1074/jbc.m111.244749
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analyses of Cryptochrome-mBMAL1 Interactions

Abstract: The mammalian cryptochromes mCRY1 and mCRY2 act as transcriptional repressors within the 24-h transcription-translational feedback loop of the circadian clock. The C-terminal tail and a preceding predicted coiled coil (CC) of the mCRYs as well as the C-terminal region of the transcription factor mBMAL1 are involved in transcriptional feedback repression. Here we show by fluorescence polarization and isothermal titration calorimetry that purified mCRY1/2CCtail proteins form stable heterodimeric complexes with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 33 publications
3
29
1
Order By: Relevance
“…The Cry1 tail region represents the most poorly conserved and least functionally and structurally characterized region of the protein. It has been shown to affect Cry1 nuclear translocation, to interact with the Bmal1 transactivation domain possibly in an acetylation-dependent fashion and to be phosphorylated in a manner that involves regulation by DNA-PK (Chaves et al, 2006; Czarna et al, 2011; Gao et al, 2013; Hirayama et al, 2007; Xu et al, 2015). Interestingly, the tail is not essential to Cry1’s ability to restore circadian cycling to arrhythmic DKO MEFs, but does modulate the period length and amplitude of the resulting oscillation (Khan et al, 2012; Li et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cry1 tail region represents the most poorly conserved and least functionally and structurally characterized region of the protein. It has been shown to affect Cry1 nuclear translocation, to interact with the Bmal1 transactivation domain possibly in an acetylation-dependent fashion and to be phosphorylated in a manner that involves regulation by DNA-PK (Chaves et al, 2006; Czarna et al, 2011; Gao et al, 2013; Hirayama et al, 2007; Xu et al, 2015). Interestingly, the tail is not essential to Cry1’s ability to restore circadian cycling to arrhythmic DKO MEFs, but does modulate the period length and amplitude of the resulting oscillation (Khan et al, 2012; Li et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Western Blotting was performed according to standard procedures using the above described antibodies as well as anti-Per2 (rabbit polyclonal, Alpha Diagnostics) anti-TATA binding protein TBP (mouse monoclonal, Abcam) and anti-α-Tubulin (mouse monoclonal, Sigma). Note on K358 Acetyl-Bmal1 antibody: Due to differences in residue numbering between Bmal1 splice variants, K538 in the reference sequence used by the vendor (Uniprot O00327-2) corresponds to the K537 residue for which acetylation has been described (Czarna et al, 2011; Hirayama et al, 2007). Blots were quantified using Image J and statistical significance was tested using paired t-tests in Prism 5 (GraphPad Software).…”
Section: Methodsmentioning
confidence: 99%
“…The PAS domains of CLOCK and BMAL1 have been implicated in PER binding [47, 63], potentially through direct interaction with the tandem PAS homodimers of PER [64, 65]. Moreover, an overlapping region on CLOCK PAS-B has been implicated in direct binding of CRY1 [66], as has a region at the C-terminus of BMAL1 [63, 67], suggesting that the architecture of the core clock protein complex may remodel throughout the day to control transcriptional output. The unstructured C-terminal regions of CLOCK and BMAL1 exhibit structural plasticity, allowing them to interact with several transcriptional regulators that control genomic targeting through chromatin remodeling and the recruitment of transcriptional machinery [66, 68, 69].…”
Section: Dynamics Of Circadian Transcriptional Regulationmentioning
confidence: 99%
“…Additionally, FRQ has been shown by a variety of methods to be an ID protein that must be stabilized by another protein, a so-called ‘Nanny,’ in order for it to function in the clock (Hurley et al, 2013). Circular dichroism demonstrated ID regions in the C-terminal signaling regions of CRY and BMAL (Czarna et al, 2011), and more recently Xu et al demonstrated the importance of disorder in the TAD of BMAL1 for interaction with CRY1 (Xu et al, 2015). In this study, the Partch lab showed that CRY1 is able to repress BMAL1 transactivation by competing with CBP (p300) for binding to the intrinsically unstructured C-terminal TAD of BMAL1, with binding eliciting dynamic conformational rearrangements.…”
mentioning
confidence: 99%